POLITICAL LANDSCAPE DYNAMICS IN POST-DECADE YEMENI REVOLUTION: A LITERATURE REVIEW - Septyanto Galan Prakoso; Ferdian Ahya Al Putra; Edo Artima Kasla (Arabic Literature Department, 2023)
During the decade following the Arab Spring and the Yemeni Revolution, significant changes and dynamics occurred in Yemen, particularly in the realms of politics and security. The current situation can be categorized as